Anterior translation of humeral head in glenohumeral joint: Comparison between limb dominance and gender using ultrasonography - Joseph L.H. (2014)
Introduction: The anterior translation of humeral head (ATHH) in glenoid cavity is one of the commonly evaluated measures to diagnose glenohumeral joint (GHJ) disorders. It is not clear that limb dominance and gender affect the ATHH in glenoid cavity. An understanding on such effects is important for clinicians to evaluate shoulder disorders. Aim: This study compares the ATHH between gender and limb dominance among healthy individuals. Material and methods: A total of 20 participants (12 females and 8 males) with mean±SD of 34±5.4 years of age participated in this study. All of the participants reported no shoulder pain, shoulder injury over the past two years, and had full range of shoulder movements at the time of testing. Participants with a history of shoulder surgery and those involved in any forms of overhead sports were excluded. A real-time ultrasonography was used to measure the ATHH in GHJ during a force of 80 N applied to GHJ. Independent sample t-test and paired sample t-test were used to analyze the differences in ATHH between limb dominance and gender. Results and discussion: The mean±SD of ATHH was 0.16±0.08 cm and 0.13±0.08 cm in dominant and non-dominant shoulder, respectively. There was no statistically significant difference in ATHH (t19=1.52, p=.14, 95% CI -0.01 to 0.07) between dominant and non-dominant shoulders. There was no significant difference in ATHH between male and female participants (t18=1.90, p=.97, 95% CI -0.08 to 0.84). Conclusions: ATHH of GHJ did not differ among genders and limb dominance in healthy participants. © 2013 Warmińsko-Mazurska Izba Lekarska w Olsztynie.